Economics of buffalo milk production in the Mathura district of Uttar Pradesh - DEOGHARE, P G; BHATTACHARYYA, N K (The Indian Journal of Animal Sciences, 2013)
An investigation was undertaken in marginal (4 ha) farms for the mixed farming in the Mathura district of Uttar Pradesh to examine the economics of buffalo milk production. Expenditure on fodder and concentrates farmed the major share in the total cost of milk production of the sample farms. Net income per buffulo per year was highest under large farms (Rs1 128.89), followed by medium farms (Rs 1 005.65). Income was low on marginal farms (Rs 756.28). Taking cost A (cask Cost and depreciation) into account overall average cost per Htre of buffalo milk was Rs 3.71. Therefore buffalo enWrprise should invariably be encouraged on marginal and small farms for increasing the farms income. Crop production contributed more than 83% to the total net income while the contribution of buffalo enterprise was around 17%.